Discussion of Accounting for Intercorporate Investments: A Behavior Field Experiment - Storey, Reed K. (Journal of Accounting Research, 1971)
Reed K. Storey, Discussion of Accounting for Intercorporate Investments: A Behavior Field Experiment, Journal of Accounting Research, Vol. 9, Empirical Research in Accounting: Selected Studies 1971 (1971), pp. 74-78